2021
DOI: 10.1021/acs.jcim.1c01078
|View full text |Cite
|
Sign up to set email alerts
|

Flexible CDOCKER: Hybrid Searching Algorithm and Scoring Function with Side Chain Conformational Entropy

Abstract: The binding of small-molecule ligands to protein or nucleic acid targets is important to numerous biological processes. Accurate prediction of the binding modes between a ligand and a macromolecule is of fundamental importance in structure-based structure–function exploration. When multiple ligands with different sizes are docked to a target receptor, it is reasonable to assume that the residues in the binding pocket may adopt alternative conformations upon interacting with the different ligands. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…It was reported that scoring functions were expected to rank the correct docking pose at the top to distinguish from the incorrect ones. 72 Based on the training set covering TMPS2 inhibitors and decoys, the AUC area under the ROC curve of the 10 scoring functions was calculated and the best scoring function LigScore2 was accordingly selected. Then, 421 docking poses of CCDs−TMPS2 complexes were re-scored and ranked according to the cutoff value (>4.995) of LigScore2.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that scoring functions were expected to rank the correct docking pose at the top to distinguish from the incorrect ones. 72 Based on the training set covering TMPS2 inhibitors and decoys, the AUC area under the ROC curve of the 10 scoring functions was calculated and the best scoring function LigScore2 was accordingly selected. Then, 421 docking poses of CCDs−TMPS2 complexes were re-scored and ranked according to the cutoff value (>4.995) of LigScore2.…”
Section: Discussionmentioning
confidence: 99%
“…The docked poses were scored using 9 generally orthogonal scoring functions (see ESI Table S3 † for cross-correlation matrix), namely, LigScore1, LigScore2, 43 Jain, 44 PLP1, PLP2, 45 PMF, PMF04, 46 CDOCKER energy and CDOCKER interaction energy. 47 Each docked pose was further scored by consensus among the same 9 scoring functions. The implemented consensus function assigns a value 1 for any molecular pose ranked within the highest 20% of certain scoring function; otherwise, it assigns the docked pose a zero value ( i.e.…”
Section: Methodsmentioning
confidence: 99%
“…For flexible receptor−flexible ligand docking with CDOCK-ER, 79 additional scripting is needed to select flexible side chains of the receptor, and to use the genetic algorithm to enhance the search for optimal docking poses. With pyCHARMM (flexible CDOCKER), these complex workflows have been compiled into a single Python module (pycharmm.cdocker) and standard docking calculations can be performed through a single pyCHARMM command (see Figure 5 and CDOCKER_WYu on the GitHub site pyCHARMM-Workshop).…”
Section: Charmm-based Simulations In Pycharmmmentioning
confidence: 99%